ISSUES OF INTRODUCING A PROCEDURE FOR ASSESSING THE EFFECTIVENESS OF TAX AND CUSTOMS BENEFITS (Academicia Globe: Inderscience Research, 2025)
The efficiency tax exemptions, the dynamic of tax preferences, and the role of tax expenditures in economic growth are given in this article. Also the lack of unique approach of estimating efficiency of tax preferences and disproportion of economic competition equilibrium in the result of tax exemptions are described. Based on international experiences and analysis in this sphere scientific-practical conclusions and proposals were developed.